Plan de implementación de nuevas áreas y servicios para el Policlínico Ochoa del cantón El Empalme provincia del Guayas - Burgos Briones, Rosa Cecilia (2012)
Implementation plans are in Marketing is a very important tool for the recovery of services, technology innovation and improvement of production processes. Project areas and implementation of new services for the Polyclinic Ochoa, is considered an important opportunity for the citizens of Splice, because through the study made favorable results were obtained justifying research. Chapter one mentions the introductory part of the project, which includes compilation contextualization of the problem, justification and definition of objectives and hypotheses. Chapter two mentions bibliographic content, the same as it performed according to the literary needs of the Project. Chapter three focuses on the materials and methods used in the investigation, which included, techniques, sources, population and research sample. Chapter four shows the results, considered favorable for the implementation of new areas and services, which led to the transformation of Polyclinic Clinic company used in research. Chapter five, shows the discussion referred to the berthing between the findings and theories of the authors who participated in the bibliographic content. Chapters six and seven indicate the conclusions and recommendations of the project prior to the completion of the proposal. Chapter eight presents the alternative proposal, because the results showed the feasibility of implementation. Chapters nine and ten, sketch the bibliography and the research